2012
DOI: 10.1371/journal.pone.0031889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insecticide Resistance on Development, Longevity and Reproduction of Field or Laboratory Selected Aedes aegypti Populations

Abstract: Aedes aegypti dispersion is the major reason for the increase in dengue transmission in South America. In Brazil, control of this mosquito strongly relies on the use of pyrethroids and organophosphates against adults and larvae, respectively. In consequence, many Ae. aegypti field populations are resistant to these compounds. Resistance has a significant adaptive value in the presence of insecticide treatment. However some selected mechanisms can influence important biological processes, leading to a high fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
150
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(159 citation statements)
references
References 30 publications
8
150
0
1
Order By: Relevance
“…Insecticide resistance, in several cases, has induced resistance fitness costs to most of the resistant individuals (Martins et al, 2012;Fang et al, 2011;Paris et al, 2011;Roy et al, 2010;Rivero et al, 2010;Djogbénou et al, 2010;Miller et al, 2009;Gassmann et al, 2009;Araujo et al, 2008;Ellison, 2007;Bourguet et al, 2004;Guillemaud et al, 2003;Foster et al, 2003;Berticat et al, 2002;Xiaoxia et al, 2001;Boivin et al, 2001;Haubruge and Arnaud, 2001;Carrière et al, 2001;Gazave et al, 2001;Oppert et al, 2000). In Benin republic, our previous studies suggested that H. armigera resistance to pyrethroids was associated with fitness cost (Djihinto et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Insecticide resistance, in several cases, has induced resistance fitness costs to most of the resistant individuals (Martins et al, 2012;Fang et al, 2011;Paris et al, 2011;Roy et al, 2010;Rivero et al, 2010;Djogbénou et al, 2010;Miller et al, 2009;Gassmann et al, 2009;Araujo et al, 2008;Ellison, 2007;Bourguet et al, 2004;Guillemaud et al, 2003;Foster et al, 2003;Berticat et al, 2002;Xiaoxia et al, 2001;Boivin et al, 2001;Haubruge and Arnaud, 2001;Carrière et al, 2001;Gazave et al, 2001;Oppert et al, 2000). In Benin republic, our previous studies suggested that H. armigera resistance to pyrethroids was associated with fitness cost (Djihinto et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A lot of cases of resistance were correlated with decrease production of eggs, and then, the resistance was costly (Martins et al, 2012;Fang et al, 2011;Paris et al, 2011;Roy et al, 2010;Xiaoxia et al, 2001). Xiaoxia et al (2001) have evaluated the effects of monocrotophos resistance on fitness of cotton bollworm, H. armigera in terms of fecundity or number of eggs laid per female of resistant and susceptible strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the prescribed range of lifetime, each larva undergoes four times skin exfoliation and turns to a pupa at the very end of the processes. An idle pupa needs to wait for 1-5 days before it metamorphoses into an adult [16]. In addition, the living adult can generally survive for 10 days, or in some extreme cases for 2-4 weeks [23].…”
Section: Introductionmentioning
confidence: 99%